Makna Kasai-Langger pada Perempuan Melayu Kelurahan Semelagi Kecil Kecamatan Singkawang Utara - Ropitriantri Ropitriantri; Pabali Musa; Endang Indri Listiani (Balale' : Jurnal Antropologi, 2021)
This study aimed to describe the Kasai-Langger Tradition, the process of Kasai-Langger Tradition, and to analyze the symbolic meaning of the material used in the Kasai-Langger Tradition. Self-cleaning for humans is one of the healthcare behaviors that has become a human habit for a long time. Malay women in Kelurahan  Semelagi Kecil have a tradition of cleaning their bodies after their menstruation is finished,  namely the Kasai-Langger Tradition. This study used the theory of the symbols Meaning of Victor Tuner because this research wanted to know the meaning of the materials used in the Kasai-Langger tradition. This study used qualitative and ethnographic methods. Data were collected using observation, interviews, and documentation. The result showed that Kasai-Langger is a traditional of mandatory bathing that must be done by Malay women in Kelurahan Semelagi Kecil after menstruation. This tradition has three process, namely the preparation of materials for the Kasai-Langger Tradition, the Kasai-Langger bathing processes, and the final process of the Kasai-Langger Tradition. This tradition has the material used meaning in the Kasai-Langger Tradition, such as Langger which means the sanctity of the body. The Kasai-Langger Tradition is a hereditary tradition that has been carried out for a long time until now.